2018
DOI: 10.1002/ppsc.201700420
|View full text |Cite
|
Sign up to set email alerts
|

Copper Template Design for the Synthesis of Bimetallic Copper–Rhodium Nanoshells through Galvanic Replacement

Abstract: metals proving extraordinarily successful, [2] there has recently been a concerted effort to adapt the same synthetic techniques to Rh-based nanostructures. [1a] By establishing control over the size, shape, and faceting of the catalyst and through the synthesis of Rh-based bimetallic architectures, it is proving possible to realize greater catalytic activity and selectivity, and hence, provides a more effective utilization of a finite precious resource.Exerting shape control over Rh nanostructures initiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…In the presence of Ni 2+ , solid Cu octahedral templates with an average edge length about 40 nm were first formed in the initial stage because of the higher reduction rate of Cu 2+ than PtCl 6 2– , which was tuned by glycine (Figure A 1 and CA 1 ). ,, The formation of Cu intermediate was characterized by XRD analysis. Because of the unstable Cu intermediate was easily oxidized under air condition, only the characteristic diffraction peak of CuO (JCPDS: 02–1040) was detected (Figure D). ,, The ICP-MS data (Figure E) also confirmed that Cu was indeed the prominent component of the solid octahedral templates (atomic ratio of Cu 93.5% and Pt 6.5%). As the reaction went on, hollow structures were gradually formed because of the replacement reaction between Cu templates and PtCl 6 2– in the aqueous. ,, Additionally, the coreduction of PtCl 6 2– (H 2 PtCl 6 ) and Cu 2+ (dissolved from solid Cu octahedron) also occurred during the replacement reaction and the resulting Pt and Cu atoms selectively deposited on the apexes whose atoms were more active than other places, leading to the growth of spiny nanothorns (Figure A 2 –A 4 and CA 2 –CA 4 ). , The emerging PtCu alloy characteristic diffraction peaks and the disappearance of CuO characteristic diffraction peak in XRD results also proved the formation of Pt composition in those intermediates during the replacement reaction (Figure D).…”
Section: Resultsmentioning
confidence: 88%
“…In the presence of Ni 2+ , solid Cu octahedral templates with an average edge length about 40 nm were first formed in the initial stage because of the higher reduction rate of Cu 2+ than PtCl 6 2– , which was tuned by glycine (Figure A 1 and CA 1 ). ,, The formation of Cu intermediate was characterized by XRD analysis. Because of the unstable Cu intermediate was easily oxidized under air condition, only the characteristic diffraction peak of CuO (JCPDS: 02–1040) was detected (Figure D). ,, The ICP-MS data (Figure E) also confirmed that Cu was indeed the prominent component of the solid octahedral templates (atomic ratio of Cu 93.5% and Pt 6.5%). As the reaction went on, hollow structures were gradually formed because of the replacement reaction between Cu templates and PtCl 6 2– in the aqueous. ,, Additionally, the coreduction of PtCl 6 2– (H 2 PtCl 6 ) and Cu 2+ (dissolved from solid Cu octahedron) also occurred during the replacement reaction and the resulting Pt and Cu atoms selectively deposited on the apexes whose atoms were more active than other places, leading to the growth of spiny nanothorns (Figure A 2 –A 4 and CA 2 –CA 4 ). , The emerging PtCu alloy characteristic diffraction peaks and the disappearance of CuO characteristic diffraction peak in XRD results also proved the formation of Pt composition in those intermediates during the replacement reaction (Figure D).…”
Section: Resultsmentioning
confidence: 88%
“…Substrate-based Cu nanostructures have previously been prepared using a number of techniques including the (i) lithographic patterning of polycrystalline films, ,, (ii) dispersal and self-assembly of colloids on surfaces, ,, and (iii) solid-state dewetting of films. , Figure shows schematic representations of the three different schemes used to form Cu nanostructures in the current study as well as SEM images of the structures obtained. The first method relies on the solid-state dewetting of an ultrathin sputter-deposited Cu film, a technique in which a heated film breaks up into nanoscale islands that then agglomerate so as to reduce the overall surface energy (Figure a).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The first method relies on the solid-state dewetting of an ultrathin sputter-deposited Cu film, a technique in which a heated film breaks up into nanoscale islands that then agglomerate so as to reduce the overall surface energy (Figure a). The structures realized are highly crystalline with a truncated nanosphere morphology (Figure b). The second method, which yields highly faceted cuboctahedra, subjects the dewetted structures formed using the first method to a liquid-phase chemical synthesis that promotes facet growth (Figure c). , The structures obtained exhibit crisp faceting characterized by prominent {100} and {111} facets (Figure d).…”
Section: Results and Discussionmentioning
confidence: 99%
“…[3] , [4] Cu has multiple advantages: it is abundant, it can catalyze a great variety of reactions [5] and it is an inexpensive metal. [6] However, the susceptibility of Cu (0) to oxidation upon exposure to air represents a big challenge for the synthesis of metallic Cu NPs Therefore, literature on Cu NPs is rather limited compared with other metallic NPs. [7] Cu displays multiple oxidation states and usually forms two stable oxides: Cu 2 O and CuO.…”
Section: Introductionmentioning
confidence: 99%